anonymous
  • anonymous
Does (x+y)^n=x^n+y^n? If not, give a counterexample.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
try replacing n with a variable. What variable makes it true? What variable makes it not true? I always start with 2.
JamesJ
  • JamesJ
Right. Try something simple, such as n = 2, and x = y = 1.
Zarkon
  • Zarkon
"Freshman's dream"

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
If I replace n with 2, I come out with \[x^2+xy+y^2 = x^2 + y^2 \]. That is not true?
JamesJ
  • JamesJ
No. Suppose x=y=1. Are the two sides equal?
anonymous
  • anonymous
Do you mean x+y?
JamesJ
  • JamesJ
and btw, \[ (x+y)^2 = x^2 + 2xy + y^2 \] No: I mean x = 1 and y =1.
Zarkon
  • Zarkon
http://en.wikipedia.org/wiki/Freshman%27s_dream
JamesJ
  • JamesJ
But without expanding it out: if x = 1 and y = 1, then x+y = 2 and thus \[ (x+y)^2 = 2^2 = 4 \] But \[ x^2 + y^2 = 1^2 + 1^2 = 1 + 1 = 2 \] Hence for n = 2 and x=y=1, is it true that \[ (x+y)^n = x^2+y^n \] ?
JamesJ
  • JamesJ
**correction: \[(x+y)^n = x^n + y^n \]
anonymous
  • anonymous
No it's not true. Did we use the Power of a Power Postulate?
JamesJ
  • JamesJ
No. Nothing so fancy was necessary.
anonymous
  • anonymous
It asks me to list what Postulate was implemented, and what do they mean by counterexample in this case?
JamesJ
  • JamesJ
You'll have to figure out what postulates were used here, given the list you have, as there's no standard list I can use to answer that for you. A counter-example of a proposition in mathematics (or logic more generally) is an explicit example of when the result does not hold and hence the proposition is not true in general. Let P be the following proposition: For all real numbers x and y and all integers n \[ (x+y)^n = x^n + y^n \ \ \ \ -- (*) \] A counter-example to this proposition P is x=y=1 and n=2, because for those values of the variables, the equation (*) does not hold. Hence the proposition P is false in general. I.e., it is NOT the case that for all real numbers x and y, and all integers n that \[ (x+y)^n = x^n + y^n \]
anonymous
  • anonymous
That clears things up a lot! Thank you very very much.
JamesJ
  • JamesJ
Sure thing

Looking for something else?

Not the answer you are looking for? Search for more explanations.